Preaching the tradition homily and hermeneutics after the exile : based on the "addresses" in Chronicles, the "speeches" in the books of Ezra and Nehemiah, and the post-exilic prophetic books - Mason, Rex 1926- (Cambridge University Press, 1990)
The aim of this study is to examine the speeches given to leading characters in the Books of Chronicles, including those which formed the basis of Gerhard von Rad's book The Levitical Sermon in the Books of Chronicles. These are compared with similar material in the Books of Ezra and Nehemiah and in the post-exilic prophets. It is Dr Mason's contention that recurring themes and homiletical devices suggest that these 'addresses' (while not to be classified as 'Sermons') do reveal something of the exegetical and teaching methods employed in the Second Temple period, which are here echoed. By studying the contents and aims of this preaching, the author tries to clarify the process by which pre-exilic Davidic Yahwism became the living faith of the post-exilic community in the challenging circumstances of the Persian and Greek periods through the careful reinterpretation of earlier scriptural material
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Bible / Chronicles / Criticism, interpretation, etc; Bible / Ezra / Criticism, interpretation, etc; Bible / Nehemiah / Criticism, interpretation, etc; Bible / Minor Prophets / Criticism, interpretation, etc; Bibel -- Zwölfprophetenbuch; Bibel -- Chronik -- 1.-2.; Bibel -- Altes Testament; Bibel; Geschichte; Judentum; Preaching / Biblical teaching; Judaism / History / Post-exilic period, 586 B.C.-210 A.D.; Predigt; Paränese